Begripsontwikkeling - Combrink, Johan (Lexikos, 1991)
Development of Concepts.This article describes ten historically parallel developments of the same type of concepts, contained in more than one Afrikaans lexeme. Such a development is e.g. one where the initial concept, "form", gave rise to a new concept, "form and content", and where this in turn gave rise to the newer concept "content". This development has taken place in the Afrikaans lexemes tuin (garden), driehoek (triangle), sirkel (circle), eier (egg, oval), kring (circle) and vierkant (square). Lexicographers are the obvious people to describe the development of concepts contained in words. Knowledge of the development of concepts is important for lexicography in two ways. Firstly, lexicographers can use their knowledge about the development of concepts heuristically while working through raw materials for dictionary entries. And secondly, users of dictionaries find it so much easier to follow an article that has been set up according to the types of development of concepts which they know (unconsciously).